Identifying the ranges of Knowledge-An effective strategy for framing Learning Outcomes - Ravishanker, M. P. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
In India the educational reforms have been periodically done through recommendation of different educational committees constituted by Government of India. Of these the National Policy on Education 1986, and the Programme of Action 1992 emphasized that Minimum Levels of Learning (MLL) should be laid down and children‟s learning should periodically be assessed to keep a track of their progress towards ensuring that “all children acquire at least the minimum levels of learning”. This was a leading twist in terms of fixed and precise educational gains for every individual learner in Indian educational system to ensure the quality of education. These recommendations fueled movement toward outcomes-based learning (OBL) in elementary, secondary, and post-secondary educational systems in India, and beyond. This movement is, in turn, influenced by a basic urge from public to ensure a greater quality and consistency within educational systems throughout the country. It can take us to a more accountable educational system and a better educated young generation. As learning outcomes focus on the end result of learning, regardless of how or where that learning occurred, their development serves to offer the potential for increased access to learning opportunities through prior learning assessment.